Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai (Studi Pada Kantor Kecamatan Ciomas Kabupaten Bogor) - Abdul Gofur; Supriyono Supriyono; Samsudin Samsudin (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2021)
This research aims to analyze the Effect of Compensation and Work Environment on Employee Performance in Kantor Kecamatan Ciomas Kabupaten Bogor. This research is a quantitative research. The data collection method was carried out by distributing questionnaires at the Ciomas Subdistrict Office, Bogor Regency, with a total of 62 respondents. Sampling used in this study using non probability sampling with saturated sampling technique. The research variables to be studied are compensation as the independent variable (X1), work environment as an independent variable (X2), and employee performance as the dependent variable (Y). The data analysis method to test this hypothesis is using multiple linear regression. Data processing uses the software program SPSS (Statistical Package for Social Sciences) version 22. Based on the results of data processing, it is found that simultaneously compensation and work environment have a significant effect on performance.